The Role of Social-Community Networks in Realizing Inclusive Education in Sekolah Alam - Rama, Ramadhanita Mustika Sari; Ibnu Azka; Muhammad Ahalla Tsauro (At-Taqaddum, 2025)
Inclusive education requires the active involvement of all social elements in creating a learning environment that adapts to the needs of all students, including children with special needs (ABK). Sekolah Alam, as an alternative education model based on nature and contextual learning, provides a strategic space for building strong social-community networks. This study aims to analyze the role of social-community networks involving parents, the community, and school administrators in supporting inclusive education practices within the Sekolah Alam environment. The research employed a qualitative method with a multi-case study design, conducted in two locations: Sekolah Alam Indonesia and Sekolah Alam Lampung. Data were collected through observation, unstructured interviews, and focus group discussions (FGDs) with school and community stakeholders. The results of this study show a shared understanding among parents, the community, and schools regarding the importance of collaboration in supporting inclusive education in Sekolah Alam. Parental participation is evident in providing facilities, engaging in academic activities, aligning educational visions, and offering financial support. The collaboration patterns in each school reflect contextual approaches based on regional characteristics: Sekolah Alam Indonesia focuses on fostering independence among children with special needs and strengthening moral values, while Sekolah Alam Lampung emphasizes developing children’s talents through an ecology-based approach. These findings enrich academic discourse on the synergy between alternative and inclusive education, while also providing empirical foundations for policymakers to strengthen the role of community networks in promoting an equitable and adaptive education system that meets the diverse needs of all learners.